Dapatkah Profitabilitas Memperkuat Pengaruh Pengungkapan Corporate Social Responsibility Dan Good Corporate Governance Terhadap Praktik Earnings Management? - Meyliana Meyliana; Vinola Herawaty (Jurnal Akademi Akuntansi, 2022)
The purpose of this study was to examine the effect of CSR disclosure by measuring the 7 themes of ISO 26000 disclosure and Good Corporate Governance on earnings management practices. In addition, this study also examines the magnitude of the effect of profitability as a moderating variable of the relationship between these variables. The testing technique uses the Random Effect Model through the Eviews 10 application. The research population is all companies that publish Sustainability Reports from 2016-2020. The results show that CSR disclosure and its interaction with profitability as a moderating variable have a positive effect on earnings management practices. On the other hand, Good Corporate Governance and its interaction with profitability as a moderating variable have no effect on earnings management practices. This study implies that CSR disclosure can attract the attention of stakeholders to company policies and practices which are solely motivated by realistic actions where earnings management practices are intended to maintain the continuity of company operations and are not intended for the benefit of management's own utility.